Antigen persistence and TLR stimulation contribute to induction of a durable HIV-1-specific neutralizing antibody response - Kenta Matsuda; Mitra Harrison; Eleanor Wettstein; Jessica Pederson; Alyssa A. Pullano; Lyuba Bolkhovitinov; Breanna Kim; Isabel Steinberg; Trevor Griesman; Sarah Stuccio; Daniel Rogan; Andy Patamawenu; et al. (Nature Communications)
Abstract HIV-1 Env glycoprotein (Env) immunogenicity is limited in part by structural instability and extensive glycan shielding and is likely the greatest obstacle to an HIV-1 vaccine. Stabilized Env trimers can elicit serum neutralizing antibodies, but the response is short-lived. Here we use Newcastle Disease Virus-like particle (NDV-VLP) platform to present stabilized versions of HIV-1 Env at high valency and in the context of varied conformational stability, adjuvants, dose, and antigen persistence. Influenza virus hemagglutinin, or SARS-CoV2 Spike-bearing VLPs rapidly induce neutralizing antibodies, in contrast, they were not induced by those bearing Env. A replicating adenovirus type 4 expressing Env rapidly induces autologous neutralizing antibodies. However, durable neutralizing antibodies are induced only when multiple features of a replicating virus infection are combined, with the largest impact from dose and escalating dose. In summary, we show here immunogenicity of HIV-1 Env could be improved by reproducing features of virus infection.